The Influence of Entrepreneurial Literacy, Farmers’ Characteristics, Creativity, and Motivation on the Success of Urban Farming Business - Welimas Kristina Parinsi; Kartika Septiary Pratiwi Musa; Dwi Anugrah Lestari Musa (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Urban farming has emerged as a strategic solution to address food security and economic opportunities in Indonesian cities. Despite its potential, urban farmers face challenges related to knowledge, skills, creativity, and motivation that influence business success. This study aims to examine the effects of entrepreneurial literacy, farmers’ characteristics, creativity, and motivation on the success of urban farming enterprises. A quantitative approach was employed, surveying 421 urban farmers who were members of local farming groups. Data were collected using questionnaires and analyzed through Structural Equation Modeling (SEM). The results indicate that entrepreneurial literacy, farmers’ characteristics, creativity, and motivation each have a positive effect on urban farming business success. These findings imply that strengthening entrepreneurial literacy, creativity, and motivation among urban farmers is essential for sustaining business performance and long-term viability. Policy interventions that focus on capacity-building programs, technical support, and resource facilitation can play a crucial role in enhancing the effectiveness and scalability of urban farming initiatives, thereby contributing to broader economic and community development.